2022
DOI: 10.1029/2022gl100079
|View full text |Cite
|
Sign up to set email alerts
|

Energy Flux Through the Magnetopause During Flux Transfer Events in Hybrid‐Vlasov 2D Simulations

Abstract: Solar wind—magnetosphere coupling drives magnetospheric dynamic phenomena by enabling energy exchange between magnetospheric and solar wind plasmas. In this study, we examine two‐dimensional noon‐midnight meridional plane simulation runs of the global hybrid‐Vlasov code Vlasiator with southward interplanetary magnetic field driving. We compute the energy flux, which consists of the Poynting flux and hydrodynamic energy flux components, through the Earth's magnetopause during flux transfer events (FTEs). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
3
1
Order By: Relevance
“…These dynamics were also seen in a study by Ala‐Lahti et al. (2022) using a 2D version of the Vlasiator code (Palmroth et al., 2018). This is in contrast with previous studies by Lu et al.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…These dynamics were also seen in a study by Ala‐Lahti et al. (2022) using a 2D version of the Vlasiator code (Palmroth et al., 2018). This is in contrast with previous studies by Lu et al.…”
Section: Introductionsupporting
confidence: 66%
“…By using the magnetic field rather than the flow field to construct the magnetopause surface, it was shown that the effect of magnetic reconnection on the dayside results in energy outflow in the form of hydrodynamic flux at X GSM > 0 and Poynting flux inflow at X GSM < 0. These dynamics were also seen in a study by Ala-Lahti et al (2022) using a 2D version of the Vlasiator code (Palmroth et al, 2018). This is in contrast with previous studies by Lu et al (2021) and H. Zhang et al (2023) who conclude that hydrodynamic flux (there referred to as mechanical energy flux) is entering the system near the magnetopause nose.…”
contrasting
confidence: 53%
“…In this study, β * = 0.1 is utilized to define the 3‐D magnetopause, consistent with Ala‐Lahti et al. (2022). (b) Views of the magnetopause from the direction of sunlight.…”
Section: Simulation Resultsmentioning
confidence: 84%
“…Physically, we may expect the magnetopause to be well approximated by an isosurface β ⋆ ∼ 1, that is, the surface where the magnetospheric magnetic pressure balances the external pressure. In practice the plasma parameters change dramatically across the magnetopause boundary, so that fixing β ⋆ to any value between 0.1 and 1.5 yields a similar result (Ala-Lahti et al, 2022;Brenner et al, 2021).…”
Section: Simulation Analysismentioning
confidence: 98%